STRATEGI HUMAS PT PUPUK ISKANDAR MUDA DALAM MENJALANKAN CORPORATE SOCIAL RESPONSIBILITY - Rina Mauliza; Ardiyanto Wardhana (Jurnal Ilmu Komunikasi AKRAB, 2023)
ABSTRACT Corporate social responsibility (CSR) is a form of companies contributing to society. CSR in its business practices leads to legal provisions, ethical values, and economic values. PT Pupuk Iskandar Muda is one of the companies that carry out CSR programs. Along with the journey of operation, the community gets many benefits including increased welfare or income, opening up employment opportunities, and fulfilling community needs. Basically CSR programs are not only material donations but also community empowerment programs. This is done so that the community can develop their quality and skills. The CSR program is designed to create a prosperous, developing and advanced society. The research uses qualitative methods with a case study approach. Researchers used structured interviews, observation and documentation methods to find data from related sources. The data were tested by using data triangulation. Triangulation in credibility testing is the examination of data from different sources at different times. The research was analyzed using the Miles and Huberman analysis interaction model, namely data collection, data reduction and conclusion drawing and verification. Based on the results of interviews, observations and documentation, the implementation of PT PIM's CSR program was obtained through four stages, namely fact finding, planning, communication and evaluation. The fact finding stage is carried out by obtaining field facts based on the results of observations and discussions with the local community. The planning stage is carried out by compiling the problems obtained in fact finding, then making detailed plans starting from the type of activity, the people involved to the budget obtained through the proposed proposal. by the community. The communication stage is carried out with the help of mass media, direct communication with village officials so that the surrounding community knows about the CSR program that will be run by PT PIM. The Evaluation stage is the final stage, in the form of an assessment by the community regarding the CSR program being implemented. Evaluation is carried out to find out whether the program is successful, continues and develops Keywords: Corporate Social Responsibility, Program, Public Relations, Strategy, PT Pupuk Iskandar Muda, .